Vaccine Hesitancy: Insights from Parents of Children with Autism Spectrum Disorder and Other Neurodevelopmental Disorders - Maslinkova, Desislava; Hristova, Mihaela; Simeonova, Dora; Avramova, Atanaska; Manolova, Harieta; Staykova, Svetla; Manolov, Lyubomir; Polnareva, Nadia (Journal of Intellectual Disability - Diagnosis and Treatment, 2026)
Vaccine hesitancy presents significant challenges and risks to public health worldwide. Certain groups, such as parents of children with Autism Spectrum Disorder (ASD), are more vulnerable to vaccine hesitancy due to concerns about safety, past controversies, and misinformation surrounding autism and immunization. This research aimed to evaluate various aspects of vaccine hesitancy among parents of children with ASD and other neurodevelopmental disorders (NDDs), highlighting key concerns that may influence their vaccination decisions. The study was based on data collected from a researcher-developed questionnaire examining parental attitudes and concerns regarding childhood vaccination. Participants included 225 parents of children diagnosed with NDD (ASD or other). Results revealed significant differences between the two groups of parents at the item, factor, and total-score levels, with the most prominent discrepancies regarding vaccine-related concerns (safety, side effects, and autism causality) and trust and acceptance of vaccination practices. However, vaccination decisions did not differ significantly by diagnosis, indicating that while attitudes and trust levels vary, vaccination behaviors remain consistent across diagnoses. Implications for practice include the need for tailored health messaging that addresses the specific fears and distrust of parents of children with neurodevelopmental disorders, particularly those with ASD. Effective communication strategies should be employed to provide emotional support, not just information, to improve vaccine acceptance and reduce hesitancy.